Peran Guru PAI dalam Meningkatkan Disiplin Belajar Siswa Melalui Metode Reward and Punishment di SMA PAB 4 Sampali: The Role of Islamic Religious Education Teachers in Improving Student Learning Discipline Through the Reward and Punishment Method at SMA PAB 4 Sampali - Aisyah Amini; Humaidah Br Hasibuan (ITScience (Information Technology and Science), 2024)
This study aims to analyze the role of Islamic Religious Education (PAI) teachers in improving student learning discipline through the reward and punishment method at SMA PAB 4 Sampali. The research method used is qualitative, with data collection techniques through interviews, observations, and documentation. In this study, researchers involved PAI teachers, students, and other respondents who were considered necessary in this study. The data analysis technique in this study used the Miles and Huberman analysis technique, consisting of four flows: da: action, data reduction, data presentation, and conclusion. After the data collection technique, the data obtained would be tested for validity using data source triangulation. The study results showed that student discipline still needed improvement, but there was an increase because less disciplined students were inspired by their friends who obeyed the rules. PAI teachers play an essential role through their approach as teachers, advisors, mediators, and evaluators. The supporting factor for discipline is a mutual agreement, such as a ban on using cell phones while studying. At the same time, the main obstacle is the negative influence of excessive cellphone use. Islamic Religious Education teachers are expected to continue innovating with a creative and balanced approach between punishment and rewards to build effective discipline in academic aspects and student character formation. The study's conclusion shows that the role of Islamic religious education teachers is to improve student learning discipline.